2008
DOI: 10.1002/chem.200800026
|View full text |Cite
|
Sign up to set email alerts
|

Energy Migration in a Self‐Assembled Nonameric Porphyrinic Molecular Box

Abstract: We describe the construction of self-assembled double-decker porphyrin arrays built up from two covalently connected trimeric Zn-porphyrin units that are joined together by metal-coordination bonds with diamine ligands. We used three different types of diamine ligands: 1,4-diaza[2.2.2]bicyclooctane (DABCO), 4,4'-bipyridine (BIPY), and 5,15-bis(4-pyridyl)-10,20-diphenylporphyrin (DPYP). The ligands act as pillars, through two axial coordination bonds with the porphyrinic Zn(II) ions, to block the planes of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 82 publications
3
51
0
Order By: Relevance
“…These ligands act as pillars via two axial coordination bonds with the porphyrinic Zn(II) ions, locking the planes of the porphyrin units in an almost cofacial orientation. 514,515 For example, treatment of Zn(II)-trisporphyrin ( 458 ) with DABCO in a 2:3 ratio led to the formation coordination cage ( 459 ; Scheme 120). Measurement of stability constants using UV-vis and 1 H NMR spectroscopic studies revealed that in presence of an excess of the ditopic N-donor ligand, these coordinations cages fall apart to give open species.…”
Section: Three Dimensional (3d) Nanoscopic Cagesmentioning
confidence: 99%
See 1 more Smart Citation
“…These ligands act as pillars via two axial coordination bonds with the porphyrinic Zn(II) ions, locking the planes of the porphyrin units in an almost cofacial orientation. 514,515 For example, treatment of Zn(II)-trisporphyrin ( 458 ) with DABCO in a 2:3 ratio led to the formation coordination cage ( 459 ; Scheme 120). Measurement of stability constants using UV-vis and 1 H NMR spectroscopic studies revealed that in presence of an excess of the ditopic N-donor ligand, these coordinations cages fall apart to give open species.…”
Section: Three Dimensional (3d) Nanoscopic Cagesmentioning
confidence: 99%
“…Photophysical studies on self-assembled Zn(II)-trisporphyrin prisms having 1,4-diazabicyclo[2.2.2]octane (DABCO), 4,4′-bipyridine and 5,15-(4-pyridyl)-10,20-phenyl-porphyrin (4′- trans -DPyP) as pillars have shown efficient photoinduced energy transfer from the triporphyrin unit to the pillars upon excitation of both components within the assemblies. 515 Luminescence experiments showed that when 4′- trans -DPyP was used as a pillar, a highly efficient photoinduced electron transfer (96% efficiency) from the trisporphyrin units to the 4′- trans -DPyP pillars occurred. The analogous trigonal prisms having ditopic N-donor ligands based on perylene tetracarboxylic acid bisimide also showed efficient photoinduced electron transfer from the Zn porphyrin units to the axially coordinated bisimide pillars, occuring from the singlet excited states localized on both chromophores.…”
Section: Miscelleneousmentioning
confidence: 99%
“…Since the past decade, there has been an increasing amount of interest in the design and synthesis of discrete 3D metallo-supramolecular architectures, as well as in their potential applications ranging from host-guest chemistry, 1,2 catalysis, [3][4][5][6] and light harvesting [7][8][9] to biology. [10][11][12][13][14][15][16][17][18][19] Three-dimensional cages, engineered via coordinationdriven self-assembly paradigms, have distinct advantages over conventional covalentcontainer molecules, owing to the synthetic ease with which the coordination cages can be assembled, the availability of a large library of building blocks, and the ability to design selective guest encapsulations.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers have attempted to construct various synthetic models of LH, [6][7][8] RC, [9,10] and their combined architectures [11] by using porphyrins. Although covalently linked cyclic porphyrin arrays accommodating an energy acceptor by multipoint coordination bonds have been constructed, [11a,c,e] a synthetic model performing energy transfer from the cyclic porphyrin arrays to the reaction center followed by charge separation, to the best of our knowledge, has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%